Economic Policy Uncertainty: Persistence and Cross-Country Linkages - Emmanuel Joel Aikins Abakah; Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper provides new evidence on the stochastic behaviour of the EPU (Economic Policy Uncertainty (EPU) index constructed by Baker et al. (2016) in six of the biggest economies (Canada, France, Japan, US, Ireland, and Sweden) over the period from January 1985 to October 2019. In particular, it uses fractional integration methods to shed light on its degree of persistence, and also carries out appropriate break tests. Further, the possible co-movement of this index between countries is examined applying a fractional cointegration method which tests for the possible existence of a long-run equilibrium relationship linking the individual indices. EPU is found to be in most cases a non-stationary, mean-reverting series which is characterised by long memory. Several breaks are also detected in each country. Finally, there is very little evidence of cross-country linkages.
Keywords: C15; C32; C51; C52; E60; 330; economic policy uncertainty; persistence; long memory; fractional integration; fractional cointegration.